Analysis of the coding genome of diffuse large B-cell lymphoma - Pasqualucci, Laura; Trifonov, Vladimir; Fabbri, Giulia; Ma, Jing; Rossi, Davide; Chiarenza, Annalisa; Wells, Victoria A; Grunn, Adina; Messina, Monica; Elliot, Oliver; Chan, Joseph; Bhagat, Govind; et al. (Nature genetics, 2011)
Laura Pasqualucci and Riccardo Dalla-Favera and colleagues report exome sequencing and copy-number analyses of diffuse large B-cell lymphomas. Their analyses identified mutations in genes not previously implicated in DLBCL pathogenesis, such as genes encoding chromatin modifiers such as MLL2. Diffuse large B-cell lymphoma (DLBCL) is the most common form of human lymphoma. Although a number of structural alterations have been associated with the pathogenesis of this malignancy, the full spectrum of genetic lesions that are present in the DLBCL genome, and therefore the identity of dysregulated cellular pathways, remains unknown. By combining next-generation sequencing and copy number analysis, we show that the DLBCL coding genome contains, on average, more than 30 clonally represented gene alterations per case. This analysis also revealed mutations in genes not previously implicated in DLBCL pathogenesis, including those regulating chromatin methylation ( MLL2 ; 24% of samples) and immune recognition by T cells. These results provide initial data on the complexity of the DLBCL coding genome and identify novel dysregulated pathways underlying its pathogenesis.